Sanctions and second home tourism: the experience of rural areas in Shemiranat, Iran - Torabi, Zabih-allah; Hall, C. Michael; Allam, Zaheer; Ghaderi, Zahed; Sharifi, Ayyoob (Journal of Policy Research in Tourism, Leisure and Events, 2024)
This study explores the impact of sanctions on the development of second home tourism in the context of a rentier state. The subject was examined with special reference to rural regions of Shemiranat County in Tehran, Iran, where second homes have developed over the past four decades. The results indicating that devaluation of the national currency, caused by the sanctions, led to turmoil in the second home market of Shemiranat. This, in turn, resulted in the development of unique and complicated relationships. Sanctions, coupled with the institutional inefficiency of the rentier state, including heavy dependence on oil-based revenues, legal loopholes, and the absence of efficient executive and supervisory institutions, have exacerbated speculation and expanded informal economies and corruption in the second home market.